EFFECTIVENESS OF SUPERVISED CHEST PHYSIOTHERAPY FOR NEONATES IN NICU WITH RESPIRATORY DISTRESS -A CASE REPORT - Soham Sudesh Sawant; Anushka Ajit Mahadik; Aishwarya Ashok Patil; Shreya Shripad Kulkarni; Dr.Sabih Khan; Dr.Aniruddha Thorat (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
DS, or neonatal respiratory distress syndrome, is a common cause of breathing problems in newborns, especially premature babies. It is caused by a lack of surfactant in the lungs, which is essential for proper lung function. The severity of RDS is often linked to the baby's gestational age, with younger and more premature infants at higher risk. The cause of neonatal respiratory distress syndrome (RDS) is a surfactant deficit brought on by either insufficient surfactant synthesis or surfactant inactivation in the setting of developing lungs. Both of these variables are impacted by premature birth, which directly contributes to RDS. Surfactant is produced at around 20 weeks of fetal life by Type 2 alveolar cells.(1)